1965
DOI: 10.1177/147715356503000301
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Luminance Basis for a Lighting Code

Abstract: Lighting codes in terms of levels of illumination incident on the visual task have served a valuable purpose for over fifty years. When based on sound principles, they are still valid for the lighting on the work. The lighting of the building interior, however, should not have to be constrained by the lighting on any specific visual task, and should be planned in relation to the design of the whole building. Experiment and observation show that the degree of satisfaction given by lighting is regulated by the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9] Others have recommended values of luminance or luminance ratios, or both between the task, task background, and walls for speci c tasks and applications. 1,[10][11][12][13][14] Mathematical relationships have been proposed to relate luminance and subjective brightness, whereby the luminance of room surfaces can be converted to subjective brightness values for use as a design tool. 6,13,[15][16][17][18] Luminaire luminance has also been identi ed as a contributing factor in the perception of environmental brightness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] Others have recommended values of luminance or luminance ratios, or both between the task, task background, and walls for speci c tasks and applications. 1,[10][11][12][13][14] Mathematical relationships have been proposed to relate luminance and subjective brightness, whereby the luminance of room surfaces can be converted to subjective brightness values for use as a design tool. 6,13,[15][16][17][18] Luminaire luminance has also been identi ed as a contributing factor in the perception of environmental brightness.…”
Section: Introductionmentioning
confidence: 99%
“…1,[10][11][12][13][14] Mathematical relationships have been proposed to relate luminance and subjective brightness, whereby the luminance of room surfaces can be converted to subjective brightness values for use as a design tool. 6,13,[15][16][17][18] Luminaire luminance has also been identi ed as a contributing factor in the perception of environmental brightness. 19 In these papers it is either explicitly stated or implicitly understood that subjective response depends on the spatial distribution of light.…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the most informative studies of apparent brightness of light sources without regard to discomfort glare were conducted by Marsden 97 as briefly mentioned above. Following the earlier work of Stevens, 108 Stevens and Marks 109 and Hopkinson, 96 Marsden showed that light source brightness perception closely followed a ‘cube root’ power law, although he empirically found the best exponent to be 0.37 rather than 0.33. 97 In other words, subjective judgements of light source brightness increased linearly with the luminance raised to an exponent of 0.37 (Figure 8).…”
Section: Vision Lighting Researchmentioning
confidence: 96%
“…To a lesser extent, brightness engineering also included perceptions of the overall amount of light reaching the observer’s eyes. This last aspect, scene brightness, was, and perhaps still is by some, termed ‘adaptation level.’ Hopkinson 96 attempted to tackle the problem of characterising adaption level, but his approach to defining adaptation level was subject to much debate, specifically how it might be photometrically measured and whether it was independent of other luminous elements in the visual field. Hopkinson thought that adaptation level should be measured simply as the illuminance at the plane of the cornea, whereas Waldram believed adaptation level was specific to the local field around the object.…”
Section: Vision Lighting Researchmentioning
confidence: 99%
See 1 more Smart Citation